Before the Bible - Newman, Judith H. (Oxford University Press, 2018)
This text reveals the landscape of scripture in an era prior to the crystallization of the Tanakh, the Jewish Bible, and before the canonization of the Christian Bible. Most accounts of the formation of the Hebrew Bible trace the origins of scripture through source-critical excavation of the archaeological 'tell' of the Bible or the text-critical analysis of the scribal hand on manuscripts, but the discoveries in the Dead Sea Scrolls have transformed our understanding of scripture formation.
10.1093/oso/9780190212216.001.0001
Keywords: Paulus; Textgenese; Kanon; Frühjudentum; Ritus; Qumrangemeinde; Schriftlichkeit; Liturgie; Judenchristentum; Urchristentum; Kollekte